Internal Conversion and Internal Pair Production, Need for New Measurements - S. Sarfarazi; M. Sohani (National Research and Innovation Agency, 2026)
The study and spectroscopy of Internal Conversion (IC) and Internal Pair Production (IPP) processes provide valuable information about nuclei and nuclear states. In the present work, Internal Conversion and Internal Pair Production processes are initially reviewed. Then, the theoretical and experimental IC coefficients, as well as the theoretical and experimental ratio of IC to IPP probabilities for the E0 transition in several isotopes are compiled and compared. The relative differences between theoretical and experimental coefficients are obtained. Significant discrepancies are observed between theoretical and experimental coefficients for several isotopes such as 101Ru, 152Gd, 58Co, 125Te, and other isotopes. These comparisons and the relative differences reveal the need for more accurate experimental measurements and improved theoretical models.